Pengaruh Produk Tabungan Dan Kualitas Pelayanan Terhadap Keputusan Menabung Nasabah Di Koperasi Kredit Bunga Tanjung Cabang Sendang Agung Lampung Tengah - Lutviana, Yusri; Hendri, Nedi; Septiani, Ana (Universitas Muhammadiyah Metro, 2024)
This research aims to find out how much influence savings products and service quality have on the decision to save at the Tanjung Bunga Credit cooperative, Sendang Agung Branch, Central Lampung. This research method is quantitative research with a population of 250 customers with a sample taken of 73 respondents as customers of the cooperative. The data collection technique uses a questionnaire as primary data and secondary data obtained from the cooperative office. The results of the research show that savings products influence customers' savings decisions at the Bunga Tanjung Credit Cooperative, Sendang Agung Branch, Central Lampung, service quality influences customers' savings decisions at the Bunga Tanjung Credit Cooperative, Sendang Agung Branch, Central Lampung, and savings products and service quality simultaneously have no influence. on customers' savings decisions at the Bunga Tanjung Credit Cooperative, Sendang Agung, Central Lampung Branch.